(untitled) (Research, Society and Development, 2021)
The text analyzes the tension between invisibility, rights and solidarity in the context of homeless people in the city of Fortaleza. The study of Weber’s legal sociology will offer concepts for understanding state legalism as the basis of ineffective formal justice for the realization of the minimum rights of people living on the streets. In the absence of the State, the Catholic Church opens its doors to exercise its solidarity role and to transform formal law into substantive law. In this perspective, this article, through exploratory research, of qualitative and quantitative nature, deductive method, collection of bibliographic-documental data, proceeded in order to carry out an analysis on the data of the national research on people on the street, the national politics for this population and the concrete experience of solidarity of the Paroquia Santíssima Trindade. Finally, it is pointed out that the results obtained lead to the conclusion that the right and care for homeless people requires emergency assistance, but, above all, institutional capacity to reconstruct links between people and society.